Utilizing Postcolonial Theory in Christian Education - Erich von Marthin Elraphoma (STFT Jakarta, Indonesia, 2021)
Postcolonial study is a method for examining a social problem or issue. It frequently uses the term subaltern to refer to groups marginalized in the social system by a hegemonic power for specific reasons, such as social class, religion, gender, race, language, and culture. The complexity of colonial effects obscures the extent to which colonialism has influenced our perspective, philosophy, and knowledge, such as regulations, policies, politics, and even our educational system that oppress others, the subaltern. This essay employs a postcolonial perspective (the subaltern theory) to demonstrate who and how people are marginalized within society’s system. Subaltern theory evolves into a way of thinking that decolonizes all spheres of life, including religious education. Furthermore, using Liam Gearon’s analysis, which examined the legal framework, educational system, and curriculum for religious education in Britain, and the marginalization within Britain’s religious education system or curriculum. This article emphasizes the need for Christian education to encourage awareness and critical thinking to change the external environment of marginalization. The author argues that subaltern theory enables Christian religious education to examine its curriculum and content to ensure that it does not perpetuate oppression but fosters critical thinking that results in in-depth reflection and uninhibited creativity to address social and theological issues.